Sorted locally confined non-negative matrix factorization in face verification - Teoh, , ABJ; Ngo, , DCL; Neo, , HF (2005)
In this paper, we propose a face recognition technique based on modification of Non-Negative Matrix Factorization (NMF) technique, which known as Sorted Locally Confined NMF (SLC-NMF). SLC-NMF used NMF to find non negative basis images, subset of them were selected according to a discriminant factor and then processed through a series of image processing operation; to yield a set of ideal locally confined salient feature basis images. SLC-NMF illustrates perfectly local salient feature region which effectively realize "recognition by parts" paradigm for face recognition. The best performance is attained by SLC-NMF compare to the PCA, NMF and local NMF, in FERET Face Database.